PHILOSOPHICAL BASIS ON EDUCATION PRINCIPLE OF TAMANSISWA IN THE BEGINNING OF ITS ESTABLISHMENT - Bonifasia Ekta Fima Natalia (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research aims to find the philosophical foundation of the article